2018
DOI: 10.1002/macp.201700530
|View full text |Cite
|
Sign up to set email alerts
|

Silicone–Epoxy‐Based Hybrid Photopolymers for 3D Printing

Abstract: In the present research, a type of cycloaliphatic silicone–epoxy resin is synthesized and then compounded with acrylates as well as photoinitiators to obtain hybrid photopolymers. The photocuring rate of the hybrid photopolymers, the morphology, thermal and mechanical properties of the cured samples with different silicone–epoxy/acrylate ratios are studied in detail. Scanning electron microscopy images prove that interpenetrating polymer network structure is formed. To improve the mechanical properties, diglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 40 publications
(57 reference statements)
1
41
0
Order By: Relevance
“…Regarding the above discussions, it can be concluded that the photoreactive polymer resin is a type of macromolecular methacrylic acid (MAA) and methyl methacrylate (MMA) mixture [70,94,[107][108][109]. Figure 43 prove that the Cu NWs and CuNi NWs embedded in the polymer matrix of the substrates manufactured by 3D printing have a facecentered cubic structure (in agreement with the database PDF-02 of the ICDD).…”
Section: Fourier-transformed Infraredsupporting
confidence: 67%
“…Regarding the above discussions, it can be concluded that the photoreactive polymer resin is a type of macromolecular methacrylic acid (MAA) and methyl methacrylate (MMA) mixture [70,94,[107][108][109]. Figure 43 prove that the Cu NWs and CuNi NWs embedded in the polymer matrix of the substrates manufactured by 3D printing have a facecentered cubic structure (in agreement with the database PDF-02 of the ICDD).…”
Section: Fourier-transformed Infraredsupporting
confidence: 67%
“…Under these conditions, the most frequently used photoinitiators for 3D printing applications are phosphine oxide‐based compounds (TPO and BAPO). [ 45–47 ] These photoinitiators have been reported in the literature for silicone‐based formulations, [ 41,42,48 ] however they do not mix well in the TRAD oligomer. Therefore, we selected a phosphine‐oxide derivate photoinitiator specifically synthesized for this approach (BAPO‐Si, Figure S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The finished products were generally rigid, brittle and prone to shrinkage and not ideal for spectacle frames or lenses. 20 However, resins with higher viscoelastic properties have been developed more recently to print objects with greater flexibility, impact resistance and more resistance to shrinkage, 21 although post-curing might be required to improve structure strength. 22 Clear resins can also be printed, 23 and are a potential material for lenses; however, to achieve optical transparency, post-processing techniques must be applied.…”
Section: Vat Photopolymerisationmentioning
confidence: 99%